2023
DOI: 10.1097/bot.0000000000002606
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Primary Arthrodesis (PA) Versus Open Reduction and Internal Fixation (ORIF) in the Treatment of Lisfranc Injuries

Abstract: Objectives: To determine whether primary arthrodesis (PA) or open reduction and internal fixation (ORIF) results in better functional outcomes through patient-reported outcome measures (PROMs). Reoperation rates and surgical characteristics among the 2 groups are evaluated as well. Design: A retrospective cohort study. Setting: Level 1 trauma center. Patients: Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This category includes 6 outcomes across 5 studies. 3,6,21,23,40 The majority of studies were statistically fragile, and only 1 study supporting no difference between ORIF and PA was found to be statistically robust. In Buda et al, 6 reoperation rates were not statistically significant between ORIF and PA with a CFI of 8 and LTF of 0.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This category includes 6 outcomes across 5 studies. 3,6,21,23,40 The majority of studies were statistically fragile, and only 1 study supporting no difference between ORIF and PA was found to be statistically robust. In Buda et al, 6 reoperation rates were not statistically significant between ORIF and PA with a CFI of 8 and LTF of 0.…”
Section: Discussionmentioning
confidence: 98%
“…Many outcomes indicated no significant difference between ORIF- and PA-managed injuries. 3,20,21,23 For example, Hawkinson et al 20 found no significant difference in “return to duty” with a robust FI of 8 and no loss to follow up in a retrospective study of 171 active duty military participants. Henning et al 21 similarly found no statistical difference in requirement of assistive device for ambulation at final follow-up between ORIF and PA with a CFI of 10 and LTF of 8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations